Background sounds and hearing-aid users: A scoping review. (2nd January 2016) - Gygi, Brian; Ann Hall, Deborah
Abstract: Objectives : A scoping review focused on background sounds and adult hearing-aid users, including aspects of aversiveness and interference. The aim was to establish the current body of knowledge, identify knowledge gaps, and to suggest possible future directions for research. Design : Data were gathered using a systematic search strategy, consistent with scoping review methodology. Study sample : Searches of public databases between 1988 and 2014 returned 1182 published records. After exclusions for duplicates and out-of- scope works, 75 records remained for further analysis. Content analysis was used to group the records into five separate themes. Results : Content analysis indicated numerous themes relating to background sounds. Five broad emergent themes addressed the development and validation of outcome instruments, satisfaction surveys, assessments of hearing-aid technology and signal processing, acclimatization to the device post-fitting, and non-auditory influences on benefit and satisfaction. Conclusions : A large proportion of hearing-aid users still find particular hearing-aid features and attributes dissatisfying when listening in background sounds. Many conclusions are limited by methodological drawbacks in study design and too many different outcome instruments. Future research needs to address these issues, while controlling for hearing-aid fitting.